Educating the Under-Served on Diabetes Prevention and Healthy Lifestyle Habits - Cantrell, Olivia (My University, 2019)
This integrated learning experience report will provide a detailed description of the internship experience fulfilled at Memphis Tilth, located in Memphis, Tennessee. Memphis Tilth is a food justice non-profit organization whose mission is to cultivate collective action for an economically sustainable, socially equitable, and environmentally sound local food system. The primary focus of this experience was to assist in educating the population served by Memphis Tilth on healthy living through a healthy diet in order to prevent diabetes or in order to simply promote healthier lifestyles. The experience was comprised of various projects that benefited the array of groups served. The projects entailed creating an outreach presentation that explains the need and benefits of the community kitchen and garden classes to the community at large; educational infographics for kitchen and garden classes that explain the nutritional benefits, growing, and cooking techniques for different seasonal produce; an educational infographic explaining the wholistic benefits of gardening; an educational infographic describing the importance of hand-washing; a lesson plan for type 2 diabetes; and a lesson template for future use. This experience with Memphis Tilth deepened my understanding of the public health challenges that exist in Memphis. Working with many of the projects within Memphis Tilth gave me a wholistic view and understanding of how to target populations in need by focusing on increasing access, affordability, and knowledge of healthy food options. To increase knowledge, educational infographics were created, and a short questionnaire was developed to gather feedback and evaluate the content, readability and cultural sensitivity of the infographs. From this experience, an understanding was gained of how to evaluate and modify educational products to best reach the intended audience. The experience that I gained working under Carole Colter and the many employees within Memphis Tilth, combined with my public health and nutrition coursework at Kansas State University, has equipped me well for a career in the field of public health.
Keywords: diabetes; nutrition; under-privileged; health inequity